2022-RA-1044-ESGO Management of early stage vulval cancer with groin sentinel lymph node sampling. A retrospective study in a cancer centre. (20th October 2022) - Katsanevakis, Emmanouil; Joshi, Anuja; Ong, Zun Zhen; O'Connor, Richard; Nunns, David; Gajjar, Ketankumar
Abstract : Introduction/Background: Groin sentinel lymph node (SLN) identification and removal has become a standard of care for women with clinical early stage vulval cancer (<4cm). There is much evidence to support safe detection of the SLN with minimal morbidity. The aims of this study is to report our experience of managing patients focusing on patient selection, adverse events, quality assurance of the procedure and any benefits and/or disadvantages to patients. Methodology: This was a retrospective study of patients treated for clinical early stage vulval cancer in a cancer centre over a 5-year period. Notes and hospital data were reviewed including admissions to emergency departments. Results: Sixty-nine patients with clinical early stage vulval cancer were included, with a mean age of 66 years. 46 patients had a wide local excision with SLN removal (23 cases with unilateral and 20 cases with bilateral SLN; missing data in 3 cases), 12 cases had a partial vulvectomy with SLN removal (7 cases with unilateral and 5 cases with bilateral SLN) and 5 patients had a radical vulvectomy with SLN removal (bilateral removal in 4 cases and unilateral in 1 case). We report a complication rate of 20% in the immediate post-operative period and 10% at 30 days post-surgery. The average length of stay was 3 days. 6 cases (8.7%) were managed as day-cases. The recurrence rate was 6.7%. A total of 160 sentinel nodes were removed, an average of 2.6 per patient. A total of 20 positive nodes were identified after histological examination. Conclusion: Since the closure of the GROINNS-2 trial we have continued with sentinel lymph node identification for women with clinical early stage vulval cancer. We have shown high level of adherence to the GROINNS trial protocol. There were a few patients managed as day-case which was of benefit to the patients.